ABC-CAG: Covering Array Generator for Pair-wise Testing Using Artificial Bee Colony Algorithm - Priti Bansal; Sangeeta Sabharwal; Nitish Mittal; Sarthak Arora (E-informatica : software engineering journal, 2016)
Testing is an indispensable part of the software development life cycle. It is performed to improve the performance, quality and reliability of the software. Various types of testing such as functional testing and structural testing are performed on software to uncover the faults caused by incorrect code, interaction of input parameters etc. One of the major factors in deciding the quality of testing is the design of relevant test cases which is very crucial for the success of testing. In this paper we concentrate on generating test cases to uncover faults caused by the interaction of input parameters. It is advisable to perform thorough testing but the number of test cases grows exponentially with the increase in number of input parameters, which makes exhaustive testing of interaction of input parameters imprudent. An alternative to exhaustive testing is combinatorial interaction testing (CIT) which requires that every t-way interaction of input parameters be covered by at least one test case. Here, we present a novel strategy ABC-CAG (Artificial Bee Colony-Covering Array Generator) based on Artificial Bee Colony (ABC) algorithm to generate covering array and mixed covering array for pair-wise testing. The proposed ABC-CAG strategy is implemented in a tool and experiments are conducted on various benchmark problems to evaluate the efficacy of the proposed approach. Experimental results show that ABC-CAG generates better/comparable results as compared to the existing state-of-the-art algorithms.